Bio-inspired design as a solution to generate creative and circular product concepts. Issue 1 (2nd January 2023) - Ruiz-Pastor, Laura; Chulvi, Vicente; Royo, Marta; Sampaio, João N.
ABSTRACT: Consumers are showing a growing concern for the environment and sustainability, while they keep their interest in more creative products that 'delight' them and exceed their expectations. Consequently, designers must meet the circular economy (CE) requirements, but also provide creative solutions. The present research describes an experiment in which a group of designers were asked to solve design problems using two different methods: random stimuli and biomimicry. The results help to answer the question regarding whether methods focused on requirements (biological requirements in this case) are as effective for obtaining creative solutions as methods oriented toward creative ideas (specifically random stimuli). The paper also examines whether biomimicry stimuli promote circularity to a sufficiently greater extent than a random stimulus to compensate for the possible loss of creativity with respect to the random method. The results show that biomimicry stimuli promote circularity in the concepts without diminishing their creativity.